Graduate employability skills within the public service: A South African case - Jonck, Petronella (The IIE, 2017)
The article reports on an evaluation of graduate employability skills as determined by public service officials within the Free State Province of South Africa. The sample included human resource management officers, directors and chief directors (n=253). A quantitative research methodology was implemented using an unabridged measuring instrument, with a reliability coefficient of 0.97 and inter-item correlation of 0.41. Results indicated that macro-vision skills are the skill set with which respondents were least satisfied followed by research skills as well as technological and environmental literacy. The graduate attributes respondents were least satisfied with were academic skills. Furthermore, the model predicted graduate employability 100%. Pursuant to the results, it is recommended that the study be extended nationally, and that results should be used to inform skills development interventions especially related to public service training.
Keywords: Graduate employability; Employability; Quantitative research; Environmental literacies; Technical literacies; Research skills; Graduate attributes